Scale of perception of family self-efficacy in home care for children on peritoneal dialysis - Lígia Simões Ferreira; Myriam Aparecida Mandetta; Maria Magda Ferreira Gomes Balieiro; Francisneide Gomes Pego do Nascimento; Maria Angélica Marcheti (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to validate an instrument for family self-efficacy perception in home care for children on peritoneal dialysis. Methods: a methodological study. The theoretical framework was presented, conducted through a literature review, field research, item development, content validity by a committee of judges and semantic analysis with families. The inter-judge agreement percentage was established at 80%, the Content Validity Index at 0.8 and the Kappa Index at 1.0. Results: the scale items were developed based on the definition of the family self-efficacy construct, covering four dimensions that correspond to the care behaviors of family members. Content validity obtained 84% agreement among judges, with a Content Validity Index of 0.84 and a total Kappa of 0.70. In semantic analysis, 100% agreement was found. Conclusions: the instrument showed good agreement among judges and the target population.